(a) The man comes to a halt in 1.99 ms = 1.99 × 10⁻³ s, so his average acceleration slowing him from 6.33 m/s to a rest is
a = (6.33 m/s - 0) / (1.99 × 10⁻³ s) ≈ 3180 m/s²
so that the average net force on the man during the landing is
F = (70.8 kg) a ≈ 225,000 N
i.e. with magnitude 225,000 N.
(b) With knees bent, the man has an average acceleration of
a = (6.33 m/s - 0) / (0.147 s) ≈ 43.1 m/s²
and hence an average net force of
F = (70.8 kg) a ≈ 3050 N
(c) The net force on the man is
∑ F = n - w = m a
where
n = magnitude of the normal force, i.e. the force of the ground pushing up on the man
w = the man's weight, m g ≈ 694 N
m = the man's mass, 70.8 kg
g = mag. of the acceleration due to gravity, 9.80 m/s²
a = the man's acceleration
Using the acceleration in part (b), we have
n = m g + m a = m (g + a)
n = (70.8 kg) (9.80 m/s² + 43.1 m/s²) ≈ 3740 N